Comorbidity of Mental and Physical Disorders - Holt, Richard I.G; Maj, Mario; Sartorius,, Norman (Karger, 2015)
This publication presents evidence about the magnitude and severe consequences of comorbidity of mental and physical illnesses from a personal and societal perspective. Leading experts address the huge burden of co-morbidity to the affected individual as well as the public health aspects, the costs to society and interaction with factors stemming from the context of socioeconomic developments. The authors discuss the clinical challenge of managing cardiovascular illnesses, cancer, infectious diseases and other physical illness when they occur with a range of mental and behavioral disorders, including substance abuse, eating disorders and anxiety. Also covered are the organization of health services, the training of different categories of health personnel and the multidisciplinary engagement necessary to prevent and manage comorbidity effectively.